REGIONAL DEVELOPMENT AND CHALLENGES FOR THE LEGAL CONSTRUCTION OF NORTHEAST - Ugeda, Luiz (Mercator, 2020)
The Northeast is a concept that is crystallized in the unconscious of the Brazilian population, designating a geographically located portion of the national territory. This article proposes to revisit the construction of this concept from a political and legal perspective, showing the choices made in each historical period to provide the intended regional development through institutions such as Chesf, DNOCS, and Codevasf, among others. The conclusion points to possible ways to reinvent the region, mainly due to the concept of the Matopiba. The study follows Geolegal methodology by using a historiographical base of the legal facts (Brazilian legislation) to produce a geographical value (regional development of the Northeast). Keywords : Codevasf, DNOCS, São Francisco River, Drought Polygon, Northeast Region, Legal Geography